PlumX As a Potential Tool to Assess the Macroscopic Multidimensional Impact of Books - Torres-Salinas, Daniel; Gumpenberger, Christian; Gorraiz, Juan (Frontiers in Research Metrics and Analytics, 2017)
The main purpose of this macro-study is to shed light on the broad impact of books. For this purpose, the impact a very large collection of books (more than 200,000) has been analysed by using PlumX, an analytical tool providing a great number of different metrics provided by various tools. Furthermore, the study focuses on the evolution of the most significant measures and indicators over time. The results show usage counts in comparison to the other metrics are quantitatively predominant. Catalogue holdings and reviews represent a book’s most characteristic measures deriving from its increased level of impact in relation to prior results. Our results also corroborate the long half-life of books within the scope of all metrics, excluding views and social media. Despite of some disadvantages, PlumX has proved to be a very helpful and promising tool for assessing the broad impact of books, especially because of how easy it is to enter the ISBN directly as well as its algorithm to aggregate all the data generated by the different ISBN variations.